Factors Influencing Teachers' Job Satisfaction A Case Study Of Public Secondry Schools In Buraidh City Saudi Arabia - Al Ajlan, Hind (Advances in Social Sciences Research Journal, 2019)
This study is conducted for the purpose of investigating the dynamics influencing teachers' job satisfaction in the public secondary schools in Buraidah. This research is quantitative; to study the factors that influence teachers’ job satisfaction at secondary public schools in Buraidah city. Data has been collected by using a questionnaire, distributed to 150 teachers in Buraidah, Saudi Arabia. Analysis and discussion of data gathered from the questionnaire is done with descriptive statistics and the use of factor analysis, correlation, reliability and multiple regression analysis to test the significant dynamics influencing teachers' job satisfaction in public secondary schools in Buraidah city. The kay results proved that, remuneration, school manager and working conditions has influence on the teachers' job satisfaction. Remuneration has the great effect on the teachers' job satisfaction at secondary public schools of the study.